The effect of vitamin D₃ supplementation on intracellular calcium and plasma membrane calcium ATPase activity in early stages of chronic kidney disease - Morvová, M; Lajdová, I; Spustová, V; Zvarík, M; Šikurová, L (Physiological research, 2014)
Chronic kidney disease (CKD) is associated with increased concentration of intracellular calcium, which is pathological and may lead to irreversible damage of cell functions and structures. The aim of our study was to investigate the impact of 6 months vitamin D(3) supplementation (14 000 IU/week) on free cytosolic calcium concentration ([Ca(2+)](i)) and on the plasma membrane calcium ATPase (PMCA) activity of patients with CKD stage 2-3. PMCA activity of patients was also compared to that of healthy volunteers. Vitamin D(3) supplementation of CKD patients resulted in the decrease of [Ca(2+)](i) (119.79+/-5.87 nmol/l vs. 105.36+/-3.59 nmol/l, n=14, P<0.001), whereas PMCA activity of CKD patients (38.75+/-22.89 nmol P(i)/mg/h) remained unchanged after vitamin D(3) supplementation (40.96+/-17.74 nmol P(i)/mg/h, n=14). PMCA activity of early stage CKD patients before supplementation of vitamin D(3), was reduced by 34 % (42.01+/-20.64 nmol P(i)/mg/h) in comparison to healthy volunteers (63.68+/-20.32 nmol P(i)/mg/h, n=28, P<0.001). These results indicate that vitamin D(3) supplementation had a lowering effect on [Ca(2+)](i) and negligible effect on PMCA activity in CKD patients.
Keywords: dospělí; Healthy Volunteers; ATPasy přenášející vápník přes plazmatickou membránu; Adult; Dietary Supplements; Renal Insufficiency, Chronic; zdraví dobrovolníci pro lékařské studie; lidé; nedostatek vitaminu D; potravní doplňky; studie případů a kontrol; vápník; chronická renální insuficience; Plasma Membrane Calcium-Transporting ATPases; Cholecalciferol; Calcium; cholekalciferol; Aged; Case-Control Studies; Vitamin D Deficiency; lidé středního věku; senioři; Middle Aged; Humans